KARAKTERISTIK KIMIA IKAN SEMBILANG ( Protosus canius ) ASIN KERING YANG DIOLAH MASYARAKAT KAMPUNG KONDA KABUPATEN SORONG SELATAN - Noya, Erinn D.; Manuhuttu, Desry M. (Pattimura University, 2025)
The sembilang catfish is a marine fish with a smooth, elongated body and no scales. In Konda Village, West Papua, sembilang fish are processed into dried salted fish. This processed fish product is preserved through salting and drying. Dried salted fish is one of the traditional fish preservation methods that remains popular today due to its practicality and distinctive taste. This study aims to determine the chemical characteristics of dried salted sembilang fish in Konda Village, South Sorong Regency. Data collection in this study was conducted through testing/experiments at the Laboratory of the Standardization and Industrial Service Center in Ambon. The research was carried out in October 2024. The results showed that the chemical characteristics met the Indonesian National Standard (SNI) 2721-1:2009, with a moisture content of 19.19% and ash content of 0.23%, except for the salt content, which exceeded 20%.